PENGAMATAN PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS LOKAL LEMBAH PALU PASCA APLIKASI BIOKOMPOS - Febiyanti; Umrah (Biocelebes, 2020)
Biocompost is an organic fertilizer term that is made from the process of decomposition of organic material through the addition of decomposers. This research has been carried out at the Botanical Gardens Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University, Palu, from March to May 2019. The research waere aimed to determine the growth and production of shallot plants Allium ascalonicum L. and the appropriate dosage of biocompost to increase the growth and production of shallot plants of A. ascalonicum L. local varieties of the valley Hammer post biocompost application. The method used in this study is Complete Randomized Design method. The results of the observations can be concluded that biocompost made from livestock waste from goat chickens, cattle with oyster mushroom waste supplements made from active Aspergillus sp. Does not increase the growth and production of onion plants due to biocompost doses that are too high. Provision of 100 and 500 grams of biocompost / polybag has the lowest tuber dry weight.